Nemoura cucurbitata (Plecoptera: Nemouridae), a new stonefly species from Guangxi, China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2020)
A new species of Nemouridae, Nemoura cucurbitata sp. nov., is described from the Maoershan National Natural Reserve of Guangxi Zhuang Autonomous Region of southern China. This new taxon is compared with related congeners.